Electronic spectroscopy, stimulated emission and persistent spectral hole-burning of cryogenic nitrogen matrices doped with tetrabenzoporphin - Arabei, S.M.; Galaup, J.-P.; McCaffrey, J.G.; Shafizadeh, N.; Crépin, C. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
This paper deal with our on-going work on the electronic spectroscopy of tetrapyrrole molecules embedded incryogenic hosts. Under nanosecond laser excitation of the free-base tetrabenzoporphin molecules in a nitrogen matrix at 8 K, increasing the laser pulse energy results in essential enhancement of the intensity of one or several vibronic emission lines to take place in the fine-structure fluorescence spectrum. The observed intense monochromatic radiation possesses characteristics of stimulated radiation being realized as a result of a transition from the purely electronic S1 level to a vibrational sublevel of the S0 state, corresponding to excitation of stretching C–C vibrations of the tetrapyrrole methane bridges. We also report on persistent spectral hole-burning effects. The analysis of the holes and antiholes formation gives some insight on the photochemical properties of tetrabenzoporphin in a nitrogen matrix.